Digital Innovation in Islamic Religious Education Learning: A Study of Flipbook Implementation - Fadhilah, Rosyida Umi; Ida Zahara Adibah; Matori (Ta'dib, 2025)
This study aims to develop and implement Flipbook media in PAI learning and evaluate its effectiveness in improving students' understanding of the topic "Imitating the Role of Ulama in Spreading Islamic Teachings in Indonesia." The research was conducted in class X Hospitality C at SMK Negeri 1 Bawen using a qualitative descriptive approach. Data collection was carried out through interviews, observations, and documentation. The results indicate that Flipbook media significantly enhances student engagement and comprehension by integrating interactive multimedia elements such as text, images, videos, and audio. Students reported increased motivation and participation, with 80% demonstrating better concept mastery compared to traditional methods. However, challenges such as limited internet access, varying levels of digital literacy, and distractions from mobile devices were identified. The discussion confirms that Flipbooks align with multimedia learning and constructivist theories, making them an effective supplementary tool for PAI education.